Efektivitas ABC Magnet Book: Studi Kuasi-Eksperimental Literasi Anak Usia 4–5 Tahun - Amal, Azizah; Nurhidayah Ilyas, Sitti; Safitri, Dian (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early literacy is a crucial foundation in early childhood education; however, many preschool children in Indonesia still face challenges due to less engaging instructional strategies. This study aimed to examine the effect of the ABC Magnet Book on the literacy skills of children aged 4–5 years at TK Bina Harapanku, Takalar. Using a quasi-experimental pretest–posttest design with an experimental group (n = 15) and a control group (n = 15), the intervention was implemented in five sessions of manipulative and multisensory learning activities. Data were collected through performance-based observations and analyzed using the Wilcoxon Signed-Rank Test. The results showed a significant improvement in the experimental group (M = 18.4 ± 2.1) compared to the control group (M = 14.2 ± 2.6), with a moderate effect size (r = 0.45; Z = −3.430; p = 0.001). A total of 33.3% of children in the experimental group reached the “Very Well Developed” category, compared to only 6.6% in the control group. These findings emphasize that play-based and interactive media are effective in fostering phonemic awareness and early literacy. Nevertheless, limitations related to the small sample size (n = 15 per group) and purposive sampling should be considered when generalizing the results. The ABC Magnet Book is recommended as an engaging and practical alternative for enhancing early literacy in preschool education